Pengaruh Motivasi Kerja Dan Kompensasi Terhadap Kinerja Karyawan Pada PT Bangor Berkembang Bersama Area Jakarta Dan Tangerang - Devianus; Maghfiroh Yanuarti (Shofanah Media Berkah, 2026)
The purpose of this study is to determine the effect of work motivation and compensation on employee performance at PT. Bangor Berkembang Bersama Area Jakarta and Tangerang partially and simultaneously. This research method uses quantitative description method, data collection technique using questionnaires. The population is 50 employees, sampling can use saturated sampling, so the sample is all employees totaling 50 employees. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis test, the results of the t-test calculation of the motivation variable (X1) with a t count of 3.973 and a significance of 0.000. Because t count is greater than t table (3.973> 2.009) and the significance is less than 5% then Ha is accepted and H0 is rejected, it can be stated that Work Motivation (X1) has a significant effect on Employee Performance (Y). Based on the results of the t-test calculation of the Compensation variable (X2) with a t count of 6.722 and a significance of 0.000. Because t count is greater than t table (6.722 > 2.009) and the significance is less than 5% (0.000) then Ha is accepted and H0 is rejected, it can be stated that Compensation (X2) has a significant effect on Employee Performance (Y). Based on the results above, namely the ANOVA test, the F count value is 55.141 while F table (0.05) for n = 47 is 2.80. So F count > from F table ( 0.05) or 55.141 > 2.80, with a significant level of 0.000 because 0.000 < 0.05, it can be said that Work Motivation (X1) and Compensation (X2) together have an effect on Employee Performance (Y).